In vitro retention force changes during cyclic dislodging of three novel attachment systems for implant overdentures with different implant angulations. Issue 4 (9th January 2020) - Maniewicz, Sabrina; Badoud, Isabelle; Herrmann, François R.; Chebib, Najla; Ammann, Patrick; Schimmel, Martin; Müller, Frauke; Srinivasan, Murali
Abstract: Objectives: This in vitro study aimed to compare changes in retentive force due to cyclic dislodging of three novel un‐splinted attachments. Materials and Methods: Experimental models simulating a mandibular two‐implant overdenture situation, with implants positioned with various interimplant discrepancies (0°, 20°, 40°, and 60°) were fabricated. Three attachment systems were tested, "N": a straight or 15°‐angulated stud; "L": a sole straight stud; and "C": a straight or individually angulated stud. All models underwent wet testing and were subjected to 10, 000 insertion–removal cycles in a universal testing machine. The mean retentive forces were calculated for cycles 10, 100, 1, 000, 5, 000, and 10, 000. Multiple mixed‐effects linear regression models were applied for statistical analyses (⍺ < 0.05). Results: "N" demonstrated an increasing retention until 1, 000 cycles, which subsequently diminished back to its initial retention at 10, 000 cycles, showing no significant loss during the entire experiment. Statistical models demonstrated no effect of implant angulation on retention, except for 60° after 10, 000 cycles ( p  < .05). "L" showed an early peak at 100 cycles and did not significantly lose retentive force before 5, 000 cycles. Angulations of 40° or higher were shown to lead to lower retentive forces (0° vs. 40° cycle 5, 000: p  < .05; 0° vs. 60° cycle 100: p  < .05, ≥cycle 1, 000: p  < .001). "C" showed stable retentive forces with no significant loss only at 10, 000 cycles (all angles: p  < .001) or 5, 000 cycles (0° vs. 60°: p  < .05). Conclusions: All systems showed retentive forces promising successful clinical use in implant overdentures, even in situations with extremely angulated implants. Specific abutments compensating interimplant angulation maintain retention longer in situations with high axe divergencies.